Key features of knowledge culture in Riau society from the 17th – 19th centuries - Muhammad, Zarina; Abdullah, Akmaliza (Human Resource Management Academic Research Society, 2023)
The Malay world and scholarly activities are inseparable. Therefore this study attempts to identify some of the essential values and characteristics of the prevailing knowledge culture in Riau society around the 17th century and peaked in the 19th century. By using the content analysis approach to some texts produced by the 19th century Riau scholar, namely Raja Ali Haji, the study will focus analysing Tuhfat Al-Nafis, Bustan al-Katibin li Al-Sibyan alMutacallimin, Thammarat al-Muhimmah Diyafat li Al-Umara’ wa Al-Kubara’ li Ahl alMahkamah and the letter of Raja Ali Haji to Von De Wall. The result of the study has shown that the knowledge culture of Riau was first, supported and enriched by religious activities and the practices of tariqah among leaders and nobles. Second, is the attitude of its leaders who love knowledge, and respect scholars and scholarly efforts that occur everywhere. Third, the presence of prominent scholars and essential works of Islamic studies. Fourth, efforts to strengthen the language among the community, particularly the Malay and Arabic languages. These features and values can serve as a guide for society in nurturing a positive intellectual culture today.